Effects of the water quantity on the solventless TEOS hydrolysis under ultrasound stimulation - Donatti, D. A.; Vollet, D. R. (Kluwer Academic Publ, 2000)
The acid hydrolysis under ultrasound stimulation of solventless tetraethoxysilane(TEOS)-water mixtures was studied at 40 degrees C, by means of a heat flux calorimetric method, as a function of the initial water/TEOS molar ratio (r) ranging from 2 to 10. The method is based on the time record of the exothermic heat peak of hydrolysis, arising after an induction time under ultrasound stimulation, which is a measure of the reaction rate. The hydrolysed quantity was found to be approximately independent of the water/TEOS molar ratio, even for r < 4. Polycondensation reaction takes place mainly for low water/TEOS molar ratio in order to supply water to allow almost complete hydrolysis. The overall process of dissolution and hydrolysis has reasonably been described by a previous modelling. The dissolution process of water in TEOS, under ultrasound stimulation and acid conditions, was found to be rather dependent of the alcohol produced in the hydrolysis reaction instead of the initial water quantity present in the mixture.
Keywords: TEOS; sono-hydrolysis; water